Identicação e caracterização de dois promotores de eucalipto: com padrão de expressão ubíquo e específico de câmbio - Fialho, Larissa Caroline [UNESP] (2013)
The rapid expansion of eucalyptus plantations observed in recent years in different Brazilian states increased the technological dependence of the culture, and its inclusion in the biotechnological context is an urgent need. For this, the availability of molecular tools that enable the production of genetically modified trees is necessary. In this context, the present work aimed to functionally characterize two promoters of Eucalyptus grandis, the first one related to a gene encoding a laccase (called EgLac) with specific expression in stem (cambium region), and the second one related to a gene encoding an ubiquitously expressed actin (called EgAct). An expression cassette containing the EgLac promoter transcriptionally fused to the GUS reporter gene was inserted into Arabidopsis thaliana, and a vascular expression pattern was observed in histochemical tests. Histological sections showed that GUS expression was restricted to the phloem of roots and leaves. In parallel, the ubiquitous expression of EgAct was validated using different eucalyptus organs/tissues, and its promoter region was amplified. An expression cassette containing the EgAct promoter fused to the GUS reporter was also inserted into A. thaliana. Histochemical analysis revealed a vascular expression of the reporter gene distributed throughout the plant. Moreover, quantification of GUS expression in transformed plants revealed variable levels of transcript accumulation according to the age and organ/tissue analyzed